New strategy in modeling and prediction of GPS satellite orbits - Elnaggar, Aly Mohamed (IJRDO-Journal of Applied Science, 2019)
The Operational Control Segment (OCS) of Global Positioning System (GPS) produce predicted navigation message which it is contain satellite ephemerides and clock corrections and utilized by receivers to calculate real-time satellite position and clock corrections for use in navigation solutions. The GPS based positioning and user accuracy are reduced in case of any errors in these ephemerides. In spite of broadcast ephemerides give satisfactory accuracy in numerous applications, they may not be sufficient for applications requiring high accuracy and it is needful to model the satellite orbit. The GPS based positioning process requires appropriate observation and prediction and computation of precise satellite orbits with adjustment techniques. Because the release period of IGS products going from around 1 day to about fourteen days which is a major disadvantage for high precision GNSS processing, this paper was done. In this paper a comparison was carried out between the satellite position calculated utilizing precise position provided by the Final Orbit solution from International GPS Service for Geodynamics (IGS), and the history broadcast ephemerides data in order to modeling and prediction of GPS satellite orbits from navigation file. The proposed method does not involve complex dynamic models, but takes full advantage of relatively mature observable history data of the orbit. The new satellite orbit prediction method is based on Fourier series and used to predict satellite orbit at some time in the future by using broadcast ephemeris history data and the satellite’s position error limited to 35 cm for the first 12 hours and this errors in predicted orbit increased to sub-meter for the second 12 hours and this errors are increased to be bigger than 5 m after 60 hours.